Inovasi Kebijakan Bisnis Untuk Meningkatkan Loyalitas Pelanggan (Studi Kasus Pada Brand Ms Glow) - Putri, Amelia; Sunarya, Erry (Jurnal Ilmiah Wahana Pendidikan, 2024)
This paper discusses business policy innovation as a strategy to enhance customer loyalty, focusing on a case study of the MS Glow brand. The research aims to analyze the role of business policy innovation in strengthening customer attachment to the brand. The results indicate that business policy innovation can be a key factor in reinforcing customer bonds, especially in beauty industries like MS Glow. Factors such as product quality improvement, responsive customer service, and adaptation to evolving market trends prove to be crucial elements in increasing customer loyalty. This paper contributes to the understanding of the significance of business policy innovation as a strategy to solidify customer loyalty in the context of the beauty industry.